2021
DOI: 10.1175/jtech-d-20-0080.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Lightning Activity Detected by WWLLN over the Tibetan Plateau and Its Comparison with LIS Lightning

Abstract: Herein, we compared data on the spatiotemporal distribution of lightning activity obtained from the World Wide Lightning Location Network (WWLLN) with that from the Lightning Imaging Sensor (LIS). The WWLLN and LIS both suggest intense lightning activity over the central and southeastern Tibetan Plateau (TP) during May–September. Meanwhile, the WWLLN indicates relatively weak lightning activity over the northeastern TP, where the LIS suggests very intense lightning activity, and it also indicates a high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…The WWLLN detects strong lightning strokes, which mainly consist of strong CG and very few IC lightning, using the time of group arrival of very low frequency (VLF) radiation from lightning (Rodger et al., 2006). The WWLLN lightning data from 2010 to 2019 are used in this study because the detection efficiency is relatively higher and more uniform over the TP during this period (Holzworth et al., 2021; Ma et al., 2021). To partially remove the bias of lightning trend caused by the changes in the station of WWLLN, detection‐efficiency‐adjusted WWLLN data were used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The WWLLN detects strong lightning strokes, which mainly consist of strong CG and very few IC lightning, using the time of group arrival of very low frequency (VLF) radiation from lightning (Rodger et al., 2006). The WWLLN lightning data from 2010 to 2019 are used in this study because the detection efficiency is relatively higher and more uniform over the TP during this period (Holzworth et al., 2021; Ma et al., 2021). To partially remove the bias of lightning trend caused by the changes in the station of WWLLN, detection‐efficiency‐adjusted WWLLN data were used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The average location accuracy of the WWLLN over the TP was ~10 km [57]. Over the midsouthern TP, the DE for CG and total flash were, respectively, 9.37% and 2.58% during 2013-2015 and continuously increased after 2015 [57,58]. Fan et al [57] also found that the CG flash data made up 71.98% of all the WWLLN flash data.…”
Section: Wwllnmentioning
confidence: 95%
“…Fan et al [57] also found that the CG flash data made up 71.98% of all the WWLLN flash data. In addition, Ma et al [58] showed that the DE of the WWLLN over the TP is generally even. Therefore, the DE and the CG percentages over the TP are similar to those over the midsouthern TP.…”
Section: Wwllnmentioning
confidence: 99%
See 1 more Smart Citation
“…The main body of Region-IV is the Tibetan Plateau, mainly including Tibet, Qinghai, southern Xinjiang, and western Sichuan. It has a highland mountain climate, and the overall geomorphic distribution trend is increasing from west to east (Ma et al, 2021). The uninhabited areas above 4500 m in elevation in the west and north of Region-IV are icy all year round, covered by snows and glaciers.…”
Section: Cg Distribution In Chinamentioning
confidence: 99%